Autonomous smart switching control for off-grid hybrid PV/battery/diesel power system. (15th November 2020) - Soudan, Bassel; Darya, Abdollah
Abstract: Operating an off-grid hybrid PV-Battery-Diesel power system requires a robust dispatch strategy to control switching between the different power sources. Most systems are operated in a reactionary manner based on instantaneous demand and available output from the different sources. This may cause output instability and possibly iterations between the components. The situation becomes more difficult when the effect of weather on PV production is taken into consideration. This work proposes three intelligent dispatch algorithms based on current system state, expected weather forecasts, and predicted available power from each source. The three algorithms prioritize different aspects of the system's performance. The algorithms were simulated under varying settings on a model designed using realistic parameters. Results show that each algorithm performs better under different conditions. Leading to a recommendation of implementing an intelligent strategy that creates the most appropriate switching schedule for a given day using predictions from all algorithms based on the weather forecasts and criteria priority. Highlights: A hybrid PV-Battery-Diesel system requires a robust dispatch strategy for switching between different components. Intelligent algorithms are proposed for producing a proactive schedule that considers weather forecasts. The proposed dispatch algorithms are simulated on an installation model based on realistic parameters. All algorithms perform better than the baseline at different aspects under different settings.